Investigation into the optimal prosthetic material for wound healing of abdominal wall defects - AKÇAKAYA, ADEM; Akcakaya, ADEM; AYDOĞDU, İBRAHİM; Aydogdu, Ibrahim; ÇİTGEZ, Bulent (My University, 2018)
The purpose of this experimental study is to investigate and compare the effects of prosthetic materials used for wound healing of abdominal wall hernias. A total of 60 rats were divided into five equal groups: Group I, control subjected to laparotomy; group II, abdominal wall defect 3x2 cm+polypropylene (PP) mesh; group III, abdominal wall defect 3x2 cm+PP mesh+hyaluronate and carboxymethylcellulose (H-CMC; Seprafilm (R)); group IV, abdominal wall defect 3x2 cm+polytetrafluoroethylene (PTFE; Composix (TM)); and group V, abdominal wall defect 3x2 cm+polyethylene terephthalate (PET; Dacron (R)). A total of 14 days after the surgery, rats were sacrificed and the meshes with the surrounding tissue were extracted in block. The breaking strength of the mesh from the fascia was recorded. The healing tissue was examined with the index of histopathology and the hydroxyproline value was analyzed using the Switzer method. Both the breaking strength and histopathological index of the wound healing were significantly improved in groups II and III compared with that in groups IV and V (P<0.001). Hydroxyproline values were the highest in group I (P<0.001). There was also a statistically significant difference between groups II and IV, and group V and the other groups (P<0.001). The present findings demonstrated that PP mesh and PP mesh+H-CMC had a superior breaking strength and improved histopathologic indices compared with PTFE and PET. Furthermore, hydroxyproline values were the lowest in the PET group. In conclusion, wound healing was improved in the PP mesh group and the PP mesh+H-CMC group compared with the PTFE and PET groups according to the present study parameters.
Keywords: incisional hernia; Mesh; Prosthetic material; Wound healing